PARAGANGLIOMA OF ORAL CAVITY - A RARE OCCURENCE - Bajpai, Manas (Journal of Ayub Medical College Abbottabad, 2020)
Paragangliomas are described as the neoplasms arise from paraganglia irrespective of their anatomical location.1 Occasionally they found outside the adrenal gland are called as extra - adrenal paragangliomas.2 The incidence of paragangliomas of head and neck have found to be associated with carotid body, the ganglion nodosum of the vagus nerve and the middle ear in most of the cases.1 The occurrence of paraganglioma in oral cavity is exceedingly rare. An exhaustive review of the literature revealed a single case of paraganglioma on an intra - oral site.3 An otherwise healthy, 37-year-old lady reported to the department of Oral and Maxillofacial pathology NIMS Dental College Jaipur (India) with a swelling on the ventral surface of the tongue. The swelling was there for one year with a gradual progression. The swelling was initially asymptomatic, but started disturbing the normal movements of the tongue from past few days. Past medical history and familial history of the patient were non - relevant to the case. Intra oral examination revealed an ovoid swelling on the ventral surface of the tongue measuring 2Ã—2 cm. (Figure-1a). The overlying mucosa was normal in colour without any surface ulceration. The swelling was non - tender and not fixed to the deeper structure. The lesion was excised surgically under local anaesthesia and excised tissue was sent for microscopical evaluation. (Figure-1b) Histopathological examination revealed, uniform polygonal chief cells arranged in round nests with granular cytoplasm showing characteristic ’˜zellballen’ appearance. (Figure-1c). Nest of polygonal cells separated by the cytoplasmic processes of sustentacular cells. (Figure-1d) The stroma was dense and fibrovascular. Laboratory investigation of urine was negative for catecholamines. The final diagnosis of extra - adrenal paraganglioma was given. One year follow up of the patient was uneventful. Paragangliomas of oral cavity are unusual and there is a paucity of literature available regarding these neoplasms in oral cavity